The Exploration of Some Challenges and Limitations of the Application of International Law on State Responsibility in the Context of Transboundary Pollution - Wongwuthikun, Krisdakorn (CMU Journal of Law and Social Sciences, 2018)
The international legal principles governing State responsibility can be applied to the issues of environmental damage, including transboundary pollution. Due to the fact that the number of cases which have been brought to international courts and tribunals relating to State responsibility is sparse, this could create uncertainties regarding the application of such principles. When applying these rules to environmental matters some theoretical problems remains unresolved, since problems of pollution and transboundary environmental damage have distinctive characteristics which can be distinguished from other general issues in international law. This article attempts to provide explanations of some difficulties and challenges in the application of international rules on state responsibility in an environmental context. Such challenges include, for example, the issue of actions or omissions that are attributable to the State, the issue of the constitution of a breach of an international obligation, the issue of the definition of the term “damage”, the issue of causation and the issue of bringing a case before international courts and tribunals for a breach of erga omes obligations.